The Gothic and theory : an Edinburgh companion - Hogle, Jerrold E.; Miles, Robert, 1953- (Edinburgh University Press, 2019)
This collection provides a thorough representation of the early and ongoing conversation between Gothic and theory - philosophical, aesthetic, psychological and cultural.
Keywords: Gothic fiction (Literary genre) -- History and criticism.; Gothic fiction (Literary genre); Criticism, interpretation, etc.